Conjuntos residenciales al margen del planeamiento en la periferia de Zaragoza - Sancho Martí, José (Geographicalia, 2017)
The question about "clandestine plotting" location in Zaragoza’s surroundings, is raised. An analysis of the factors which have taken part in this process and its spatial distribution is mude. The high number of users demands alternative solutiom and legalization channels